Developing a Qur’anic Ethnopedagogical Curriculum Model through the Integration of Minangkabau Local Wisdom in Islamic Religious Education - Ahmad Saefulloh; Syafrul Nalus; Syamsuri Yusup; Zakia Zuzanti; Asyraf Isyraqi Bin Jamil (Universitas Muhammadiyah Mataram, 2026)
The growing interest in culturally responsive education has encouraged educators to seek meaningful ways of connecting religious values with local wisdom in formal learning. However, little attention has been given to understanding how religious teachings are systematically translated into culturally relevant curriculum practices. This study examines the integration of Qur’anic values and Minangkabau local wisdom in Islamic religious education and develops a Qur’anic ethnopedagogical curriculum model based on curriculum documents. Using a qualitative document analysis approach, the study analyzed Islamic Religious Education lesson plans that explicitly integrated Qur’anic teachings with Minangkabau cultural values. The documents were selected purposively and examined through thematic coding, categorization, and pattern identification using a document analysis matrix. The findings reveal four interrelated themes: the contextualization of Qur’anic values through local wisdom, character-oriented curriculum integration, the role of Adat Basandi Syarak, Syarak Basandi Kitabullah (ABS-SBK) as a curricular foundation, and the development of a Qur’anic ethnopedagogical curriculum model. The results show that local culture functions not merely as cultural content but as a pedagogical pathway through which religious values are understood, contextualized, and internalized in meaningful learning experiences. These findings highlight the potential of culturally grounded curriculum design to strengthen character education while preserving the relevance of religious learning. Unlike previous studies that primarily focus on the integration of local wisdom or character education outcomes, this study offers a curriculum-level explanation of how religious values are transformed into culturally meaningful educational experiences. Future research should examine the model's implementation in classroom settings and explore its applicability across different cultural contexts.